Voriconazole in Treatment of Resistant Fungal Keratitis: Doi:10.36351/pjo.v36i4.1002 - Riaz, Sidrah; Khan, Muhammad Tariq; Mehmood, Khalid; Hussain, Mahfooz; Riaz, Sara (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the effect of intrastromal Voriconazole for treatment of resistant fungal keratitis in a tertiary care eye hospital in Lahore, Pakistan. Study Design: Experimental interventional study. Place and Duration of Study: Avicenna Medical College Hospital, Lahore, from July 2017 to July 2019. Methods: Sixty four patients were selected. All patients with fugal keratitis were included. The patients with previous corneal scar, mature cataract, endophthalmitis, Panophthalmitis, scleral involvement, impending or frank corneal perforation and uncontrolled diabetic patientswere excluded.Corneal scrapings of all patients were sent for 10% KOH staining. All patients were given intrastromal Voriconazole at 3 to 4 sites in divided doses in one ml syringe with 27-guage needle. Injection was repeated on 4th and 8th day. It was combined by topical antifungal and antibiotic eye drops six hourly. Patients were followed at day two, five, nine, three weeks and at 3 months. Results: There were 55 males and 9 females. Average size of ulcer was 6.4mm ranging from 5.5mm ± 1.8mm. Fifty six (88%) patient showed improvement while eight (12%) patients ended up in melting of cornea which was managed with tectonic corneal graft. In three (5%) patients penetrating Keratoplasty was done. Conjunctival congestion and ocular pain improved significantly one week after third dose but final visual acuity was not significantly improved due to scarring. Conclusion: The intrastromal corneal voriconazole is an effective treatment for fungal keratitis in term of healing corneal ulcer, control of infection and saving of eye from corneal perforation and permanent blindness. Key Words: Voriconazole, Fungal keratitis, Penetrating Keratoplasty.